Penyuluhan Keselamatan dan Kesehatan Kerja (K3) Bagi Anggota Koperasi Sangihe Mang Sunaung, Kampung Mahumu 1, Kabupaten Kepulauan Sangihe - Kasaluhe, Meityn Disye; Rieuwpassa, Frets Jonas; Cahyono, Eko; Berhimpon, Siegfried; Sambeka, Yana; Tanod, Wendy Alexander; Ansar, Novalina Maya Sari; Makisake, Nadia Arlina; Kundiman, Gita Artika Putri; Tengkue, Florenza Puspa Indah; Maalua, Sheyla; Kendek, Tasya Jenifel; Mandiangan, Meyrijean (Abdimas Indonesian Journal, 2024)
The quality of workers' health will decrease when there is no protection of occupational safety and health (K3). The decreasing quality of health will certainly have an impact on worker productivity, decreased job satisfaction and even increased the risk of work accidents. K3 counseling for members of the Sangihe Mang Sunaung Cooperative, namely to provide knowledge and skills for cooperative members in implementing a safe and healthy work environment and behavior. This activity is carried out in several stages, namely initial exploration and observation, coordination and determination of implementation, implementation and evaluation. The evaluation results showed an increase in participant knowledge after the K3 counseling was carried out. The post-test scores of participants were higher than the pre-test scores. This shows that the K3 counseling activities can be well understood and have a positive impact on increasing the knowledge of Sangihe Mang Sunaung cooperative members about occupational safety and health (K3)